Study on relationships between coal fractal characteristics and coal and gas outburst - Zhang, S.; Yang, S.; Cheng, Jianwei; Zhang, B.; Lu, C. (2011)
The influence factors for the coal and gas outburst can be divided into two categories. They are external factors and internal factors, respectively. The external factors include in-seam gas pressure, geological structure and so on, while the internal factors are mainly the coal characteristics themselves. Currently, researchers have already agreed that the in-seam gas pressure and the geological structure are two very important factors to induce the propensity of the coal and gas outburst. Generally, the higher in-seam gas pressure and the more complicated geological structures are, the greater risk of the coal and gas outburst is. However, it is still unknown that the relationships between coal characteristics and the potential risk outburst, especially the microstructure of coal. In this paper, the mercury intrusion method and the Langmuir isotherm adsorption method are used to study the coal fractal characteristics. By comparing the relationships between the fractal dimension and outburst feature parameters based on various coal samples, the experimental results show that the fractal dimension D1 has a negative correlation with the coal strength while the fractal dimension D 2 has also a negative correlation with the gas releasing speed. Based on the results, a new index" d", which is the mathematical difference of the driving force and resistance of the outburst, is proposed to predict the coal and gas outburst propensity. It also could be served as a new tool in managing the coal mine safety. © 2011 Published by Elsevier Ltd.